2018
DOI: 10.4018/ijfsa.2018070104
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Soft Matrices Entropy

Abstract: This article describes how information technology and internet together infused organizations with huge amount of data. Consequently, accumulating, storing, understanding and analyzing data at a large scale is equally important and complex. Out of this data not all is information data, in order to extract information, one needs to discard redundant, irrelevant and unnecessary data. This article aims to introduce a data reduction technique which will be useful to discard irrelevant data. Here in data-reduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Khan and Pal [8] introduced the generalised inverses of intuitionistic fuzzy matrices. For fuzzy soft matrices, Sharma et al [16] suggested a logarithmic entropy measure for fuzzy soft matrix and provided its application in decision making and data reduction problems. Inspired by the above work in the field of fuzzy matrices, in this paper, here we propose a parametric generalized logarithmic divergence measure for intuitionistic fuzzy matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Pal [8] introduced the generalised inverses of intuitionistic fuzzy matrices. For fuzzy soft matrices, Sharma et al [16] suggested a logarithmic entropy measure for fuzzy soft matrix and provided its application in decision making and data reduction problems. Inspired by the above work in the field of fuzzy matrices, in this paper, here we propose a parametric generalized logarithmic divergence measure for intuitionistic fuzzy matrices.…”
Section: Introductionmentioning
confidence: 99%